KETIMPANGAN DALAM PENERAPAN HUKUM PERKAWINAN ANTARAGAMA DI INDONESIA: ANALISIS DAN SOLUSI - Pikahulan, Rustam Magun; Umar, Nasaruddin; Haryanti, Tuti (LPPM Universitas Bina Insan, 2025)
Interfaith marriage in Indonesia has become a complex legal issue with legal disparities between the Marriage Law and the Population Administration Law. The Marriage Law affirms that marriage is valid if conducted according to each religion's law, while the Population Administration Law allows interfaith marriages to be legalized through court decisions. This disparity creates legal uncertainty in Indonesia, as evidenced by differing legal interpretations by judges at various court levels. This research uses normative legal methods with legislative, conceptual, and case approaches to analyze this phenomenon and find solutions. The research findings suggest the need for harmonization between marriage law and population administration. A short-term solution involves issuing Supreme Court regulations that align with religious values, while a long-term solution requires legal reforms to synchronize regulations, ensuring legal certainty for interfaith marriages in Indonesia.